Yield and apparent dry matter and nitrogen balances for muskmelon in a long-term comparison between an organic and a conventional low input cropping system - Farneselli, Michela; Benincasa, Paolo; Bonciarelli, Umberto; Tosti, Giacomo; Tei, Francesco; Guiducci, Marcello (Italian Journal of Agronomy, 2015)
Nine-year yields and apparent balances of dry matter and nitrogen (N) are reported for muskmelon cultivated in a long-term comparison trial between an organic and a conventional low input system in Central Italy. In every year, yield, above ground biomass and N accumulation of each cash crop, green manure and weeds, and the partitioning between marketable yield and crop residues were determined. Apparent dry matter and nitrogen balances were calculated at the end of each crop cycle by taking into account the amounts of dry matter and ex novo N supplied to the system as green manure legume Ndfa (i.e., an estimate of N derived from the atmosphere via symbiotic fixation) and fertilisers, and those removed with marketable yield. Differences between systems varied across years. On average, organic muskmelon yielded 16% less than the conventional one, while the fruit quality was similar in the two cropping systems. Fruit ripening began one week later and it was more scaled than in the crop grown conventionally. This was the consequence of a slow initial growth of the organic crop, due to inadequate green manure N total supply or timing of N release. Moreover such a wide spaced crop (0.5 plants m–2, in rows 2 m apart) was not efficient in intercepting N released from green manure biomass incorporated broadcast. Compared to the conventional crop management, the organic crop management resulted in much higher organic matter supply to the soil and in higher residual N after harvest. Thus, the choice of cultivating wheat just after melon to prevent postharvest residual N loss appears a key strategy especially in organic systems. Fall-winter green manure crops contributed to the self-sufficiency of the organic system by supplying muskmelon with either N absorbed from the soil or ex novo legume Ndfa.